2021
DOI: 10.1152/ajpheart.00225.2021
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol: striking the cardiovascular system by harming the gut microbiota

Abstract: Ethanol consumption represents a significant public health problem, and excessive ethanol intake is a risk factor for cardiovascular disease (CVD), one of the leading causes of death and disability worldwide. The mechanisms underlying the effects of ethanol on the cardiovascular system are complex and not fully comprehended. The gut microbiota and their metabolites are indispensable symbionts essential for health and homeostasis and therefore, have emerged as potential contributors to ethanol-induced cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 219 publications
(350 reference statements)
2
0
0
Order By: Relevance
“…It was also reported that alcohol intake was positively correlated with peripheral atherosclerotic plaque volume, 26 suggesting that heavy consumption may result in macrovascular diseases. Recently, it was reported that alcohol‐induced imbalances in the symbiotic relationship between the host and the gut microbiota could lead to the development and progression of CVD 27 . In the present study, we also found that occasional drinking could more significantly decrease all‐cause mortality compared with never drinking, indicating that drinking less than once a week may have a positive effect on health outcomes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It was also reported that alcohol intake was positively correlated with peripheral atherosclerotic plaque volume, 26 suggesting that heavy consumption may result in macrovascular diseases. Recently, it was reported that alcohol‐induced imbalances in the symbiotic relationship between the host and the gut microbiota could lead to the development and progression of CVD 27 . In the present study, we also found that occasional drinking could more significantly decrease all‐cause mortality compared with never drinking, indicating that drinking less than once a week may have a positive effect on health outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, it was reported that alcohol-induced imbalances in the symbiotic relationship between the host and the gut microbiota could lead to the development and progression of CVD. 27 In the present study, we also found that occasional drinking could more significantly decrease all-cause mortality compared with never drinking, indicating that drinking less than once a week may have a positive effect on health outcomes. However, no association was found between light or moderate alcohol consumption and the outcomes.…”
Section: Discussionsupporting
confidence: 72%